Intervención del instrumento doloso no cualificado en los delitos de correspondencia - Núñez Custodio, Nicole (2024)
This paper discusses the involvement of the third party in the crimes of passive bribery and generic active bribery, emphasizing the importance of considering the theory of the unqualified intentional instrument to guarantee proportionality in the imposition of penalties. Additionally, it analyzes how the mere use of complicity affects the third party who participates in correspondence crimes especially in the aforementioned cases of bribery.It examines the different ways in which the third party can be considered an accomplice and the legal implications that this entails, underlining the need for a new doctrinal interpretation to guarantee a penological proportionality. The inclusion of the third-party figure in bribery crimes poses challenges for the judicial system, as it implies evaluating their degree of responsibility and their relationship with the main actors of the crime. In this sense, a thorough review of complicity criteria and greater clarity in its application are proposed to ensure fairness and coherent justice.